(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
This article covers the theoretical foundations of the formation and development of students’ physical qualities - strength, endurance, agility, speed, and flexibility, as well as effective forms and methods of their improvement based on modern pedagogical technologies. The advantages of monitoring using innovative technologies used in school education and sports institutions, as well as digital tools, are scientifically analyzed. The results of this study have practical significance in increasing the effectiveness of physical education classes.